Forest and agricultural land change in the Carpathian region—A meta-analysis of long-term patterns and drivers of change - Munteanu, Catalina; Kuemmerle, Tobias; Boltiziar, Martin; Butsic, Van; Gimmi, Urs; Lúboš Halada; Kaim, Dominik; Király, Géza; Konkoly-Gyuró, Éva; Kozak, Jacek; Lieskovský, Juraj; Mojses, Matej; et al. (Land use policy, 2014)
•Long-term assessment of 250 years of agricultural and forest cover change.•Meta-analysis of 66 publications describing 102 locations across the Carpathians.•Agricultural expansion before World War I, decrease after the collapse of Socialism.•Forest transition during the Interwar period, rapid forest cover increase after 1990.•Deforestation driven by institutions and economies, abandonment by socio-demographics. Humans have altered land cover for centuries, and land-cover change is a main component of global change. Land use transition trajectories, such as the forest transition theory (i.e. switch from deforestation to stable or increasing forest cover), relate long term changes in land use to gradual changes in underlying drivers, such as economic development, demographic change, and urbanization. However, because only few studies examined land change over centuries, it is not clear how land cover changes during very long time-periods which are punctuated by shifts in socio-economics and policies, such as wars. Our goal here was to examine broad land change patterns and processes, and their main driving forces in Central and Eastern Europe during distinct periods of the past 250 years. We conducted a meta-analysis of 66 publications describing 102 case study locations and quantified the main forest and agricultural changes in the Carpathian region since the 18th century. These studies captured gradual changes since the peak of the Austro-Hungarian Empire up to the accession to the European Union of most of the formerly socialist countries in the study region. Agricultural land-use increased during the Austro-Hungarian Empire in 70% of the case studies, but dropped sharply during and especially after the collapse of the Socialism (over 70% of the cases). The highest rates of abandonment occurred between 1990 and 2000. The Carpathian region experienced forest transition during the Interwar period (93% of the cases), and the forest expansion trend persisted after the collapse of Socialism (70% of the cases). In terms of the drivers, institutional and economic factors were most influential in shaping deforestation and agricultural expansion, while socio-demographics and institutional shifts were the key drivers of land abandonment. Our study highlights the drastic effects that socio-economic and institutional changes can have on land-use and land-cover change, and the value of longitudinal studies of land change to uncover these effects.